1987
DOI: 10.1002/dev.420200507
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of an endogenous, nonopioid and hormonally mediated analgesic system

Abstract: Rats of different ages (10-day, 28-day, and 3-month-old) were exposed to cold-water stress in order to activate an endogenous analgesic system. The effects of naltrexone (7 mg/kg) and dexamethasone (.4 mg/kg) were also studied to examine the role of the opioid and hormonal systems in cold-water-induced analgesia. Following cold-water exposure, nociception was measured with the tail-flick procedure for 2 hr. Results revealed that cold water produced a significant level of analgesia in the 10-day, 28-day, and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Short warm water swims in our study produced SIA in 20 and 25 day old rats confirming other ontogenetic studies using maternal deprivation (Kehoe & Blass, 1986), electric shock (Hamm & Knisely, 1984) and cold water swimming (Hamm & Knisely, 1987) as stressors. The temperature and duration of swimming has been shown in adult rats to alter markedly the neurochemical basis of the SIA.…”
Section: Discussionsupporting
confidence: 91%
“…Short warm water swims in our study produced SIA in 20 and 25 day old rats confirming other ontogenetic studies using maternal deprivation (Kehoe & Blass, 1986), electric shock (Hamm & Knisely, 1984) and cold water swimming (Hamm & Knisely, 1987) as stressors. The temperature and duration of swimming has been shown in adult rats to alter markedly the neurochemical basis of the SIA.…”
Section: Discussionsupporting
confidence: 91%
“…The age-related differences in this study were shown to be non-opioid mediated but were NMDA receptor dependent. Other studies suggest, however, that non-opioid mediated SIA which is potentiated following adrenalectomy, is not age-specific (Hamm and Knisely, 1987;Hamm et al, 1986). A study with human volunteers shows an agerelated decline in SIA (Washington et al, 2000).…”
Section: The Effects Of Age and Experience On Siamentioning
confidence: 94%
“…It is noteworthy that others (Hamm & Knisely, 1987) did not report such potentiation of analgesia produced by water immersion. It is likely that this difference in results stems from differences in procedures.…”
Section: Discussionmentioning
confidence: 93%
“…However, cold-water immersion was found to produce reductions in core temperature in pups that were inversely correlated with age (Hamm & Knisely, 1987). If a reduction in core temperature would therefore cause the analgesic response, 3-day-old pups should display more analgesia following immersion in water than older animals.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation